PEMANFAATAN FITUR INSTAGRAM SEBAGAI SARANA KOMUNIKASI PEMASARAN KEDAI BABAKKEROYOKAN DI KOTA PALU - Antasari, Citra; Pratiwi, Renystiyah Dwi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
This study aims to determine the use of Instagram as a means of marketing communication for Babakkeroyokan in Palu City. This research method is descriptive qualitative by conducting data collection techniques, conducting observations, structured interviews with three informants who have been selected through purposive sampling technique. The number of informants in this study consisted of three informants, namely the owner and holder of the Instagram, the manager of the Instagram, and the Babakkeroyokan sales team. Data analysis techniques used in the form of data collection, data reduction, data presentation, and drawingconclusions. Features Instagram used by Babakkeroyokan have eleven features, namely Profile and Bio Features, Photo and Video Upload Features, Stories Features Caption Features, Comments Features, Hastags Features, Like Features, Activity Features, DirectMessage (DM) Features, Geotagging (Location Tag) Features, and finally the Story Archive Feature. These features are used by Babakkeroyokan as tools to promote their food products to consumers. Features Instagram used by Babakkeroyokan have their respective benefits and uses in helping Babakkeroyokan to promote their food products to consumers, these features are used well by Babakkeroyokan as a means of information to consumers and have benefits for Babakkeroyokan sales in increasing their sales against the same business competition as them. In the use of these features there are interactions with consumers that make communication occur, of the eleven Instagram used by Babakkeroyokan, there are several features that are used every day to promote their food products and interactions with consumers so that communication is established, namely the Story andfeature Direct Message (DM).